2016
DOI: 10.5935/0101-2800.20160052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neuromuscular electrical stimulation on functional capacity of patients with chronic kidney disease on hemodialysis

Abstract: Electrical neuromuscular stimulation had a positive impact on pulmonary function and functional capacity, leading to better physical performance in patients on hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 0 publications
1
25
2
4
Order By: Relevance
“…Therefore, 6 MWT represents valuable diagnostic tool for fitness testing in these patients . Results of this study fully agree with the results of recent studies, which reported significant increase in walked distance and improvement of functional parameters after NMES in patients on HD . Regardless of indisputable NMES benefits which were proven in this study, some expectations were not met.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, 6 MWT represents valuable diagnostic tool for fitness testing in these patients . Results of this study fully agree with the results of recent studies, which reported significant increase in walked distance and improvement of functional parameters after NMES in patients on HD . Regardless of indisputable NMES benefits which were proven in this study, some expectations were not met.…”
Section: Discussionsupporting
confidence: 87%
“…43 Results of this study fully agree with the results of recent studies, which reported significant increase in walked distance and improvement of functional parameters after NMES in patients on HD. 28,29,41,44 Regardless of indisputable NMES benefits which were proven in this study, some expectations were not met. First, it concerns the measurement of arterial stiffness, which was one of the primary goals of the study due to the fact that cardiovascular complications represent major cause of mortality in dialyzed patients.…”
Section: Discussionmentioning
confidence: 75%
“…Apesar dos fatores de risco cardiovascular, os pacientes do presente estudo apresentaram um bom desempenho na avaliação físico funcional e cardiorrespiratória. Pacientes que realizam hemodiálise e não estão cadastrados em lista de espera apresentaram menor desempenho na avaliação da força muscular respiratória 7,8 . Pacientes com doença renal crônica em hemodiálise 7 e que ainda não iniciaram o tratamento dialítico 9 também apresentaram desempenho funcional inferior no TC6'.…”
Section: Tabela 3 Correlação Do Tempo De Doença Renal E Tempo Em Lisunclassified
“…Apesar dos avanços nos procedimentos de diálise, os pacientes que fazem esse tratamento apresentam baixa tolerância ao exercício, o que leva ao descondicionamento físico, fator esse relacionado a comorbidades e que também pode estar associado ao tempo de permanência dos pacientes em lista de espera pelo transplante renal [7][8][9] . Vários estudos avaliaram a capacidade funcional de pacientes em tratamento dialítico [7][8][9] , porém nenhum deles estratificou esta análise de acordo com o tempo dos pacientes em lista de espera para o transplante renal. Portanto, o objetivo deste estudo foi descrever as características físicas, antropométricas e cardiorrespiratórias de pacientes em lista de espera, que aguardavam para realizar o transplante renal, assim como, analisar as variáveis de acordo com o tempo de espera pelo transplante renal e tempo de doença renal crônica.…”
Section: Introductionunclassified
“…Nesse sentido, pode-se inferir que o comprometimento muscular na doença renal não ocorre somente na musculatura periférica existe também um acometimento nos músculos respiratórios, com significativa redução das propriedades de endurance, força e potência, consequente da miopatia urêmica, interferindo no trabalho respiratório contribuindo para a diminuição das capacidades pulmonares 16 .…”
unclassified